Determinacão do período orbital de sistemas binários clipsantes - Osório, Yeisson Fabian Martinez (2009)
In this work is presented a new method for the determination of the orbital period (Porb) of eclipsing binary systems based on the wavelet technique. This method is applied on 18 eclipsing binary systems detected by the CoRoT (Convection Rotation and planetary transits) satellite. The periods obtained by wavelet were compared with those obtained by the conventional methods: box Fitting (EEBLS) for detached and semi-detached eclipsing binaries; and polynomial methods (ANOVA) for contact binary systems. Comparing the phase diagrams obtained by the different techniques the wavelet method determine better Porb compared with EEBLS. In the case of contact binary systems the wavelet method shows most of the times better results than the ANOVA method but when the number of data per orbital cicle is small ANOVA gives more accurate results. Thus, the wavelet technique seems to be a great tool for the analysis of data with the quality and precision given by CoRoT and the incoming photometric missions.